2018
DOI: 10.18500/1684-7318-2018-3-251-258
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Burrowing of the Common Hamster (Cricetus cricetus L., 1758) (Rodentia: Cricetidae) in the City

Abstract: The Common hamster (Cricetus cricetus) has been intensively colonizing cities during the last decades. Changes in the burrow numbers and their distribution over an area might be important indicators of the population status for the Common hamster in an urban environment. In this study, we consider the character of the burrow distribution on the experimental plot (2.2 ha) situated in the park of Simferopol City, Russian Federation. The brushwood and tree vegetation on this plot had been previously mapped in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
2
0
3
Order By: Relevance
“…None of the most common burrowing animal families were reported to be active from November until February. (Eccard and Herde, 2013;Jimenez et al, 1992;Katzman et al, 2018;Malizia, 1998;Monteverde and Piudo, 2011). This is also in line with our observations because burrowing intensity increased from March until May, reached its peak between May and June, and declined until September (Fig.…”
Section: The Role Of Climate Variability and Burrowing Cyclessupporting
confidence: 92%
“…None of the most common burrowing animal families were reported to be active from November until February. (Eccard and Herde, 2013;Jimenez et al, 1992;Katzman et al, 2018;Malizia, 1998;Monteverde and Piudo, 2011). This is also in line with our observations because burrowing intensity increased from March until May, reached its peak between May and June, and declined until September (Fig.…”
Section: The Role Of Climate Variability and Burrowing Cyclessupporting
confidence: 92%
“…Also, previous field based studies observed an increased bioturbation activity with higher (Milstead et al, 2007;Meserve, 1981;Tews et al, 2004;Wu et al, 2021;Ferro and Barquez, 2009), but also with lower vegetation cover (Simonetti, 1989;Zhang et al, 2020;Zhang et al, 2019;Qin et al, 2021). Furthermore, soil mixing rates are not homogenous throughout the year but depend on the animal phenological cycles (Eccard and Herde, 2013;Jimenez et al, 1992;Katzman et al, 2018;Malizia, 1998;Morgan and Duzant, 2008;Monteverde and Piudo, 2011;Gray et al, 2020;Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Древесно-кустарниковая растительность площадки включает элементы регулярно посаженных 50 -60 лет назад аллей и участки с бессистемно расположенными растениями (Katzman et al, 2018). За 6-летний период исследований территория парка претерпела значительные изменения в результате проводимой рекультивации и строительства дополнительных объектов садово-парковой инфраструктуры.…”
Section: материал и методыunclassified
“…Это может свидетельствовать о том, что если обыкновенные хомяки поселяются поблизости друг от друга (то есть образуют кластер из норных элементов), то они обычно привязаны к отдельным деревьям. Факты взаимосвязи расположения агрегаций нор обыкновенного хомяка с расположением стволов деревьев в пространстве отмечались при исследовании существования вида в урбоценозах Западной Европы и в нашей предыдущей работе, в которой данная закономерность была установлена другими методами (Katzman et al, 2018). Предполагалось, корневые системы деревьев обеспечивают конструктивную устойчивость систем нор.…”
Section: рис 3 проективное покрытие кустарникового ярусаunclassified
See 1 more Smart Citation